A tale of two spins: electron spin centre assemblies with N@C60 for use in QIP - Farrington, BJ (2014)
Quantum information processing (QIP) has the potential to reduce the complexity of many classically ‘hard’ computational problems. To implement quantum information algorithms, a suitable physical quantum computer architecture must be identified. One approach is to store quantum information in the electron spins of an array of paramagnetic N@C60 endohedral fullerene molecules, using the electron-electron dipolar interaction to permit the formation of the entangled quantum states needed to implement QIP. This thesis explores two different chemical methods to create two-spin centre arrays that contain N@C60. The first method uses a double 2,3 dipolar cycloaddition reaction to a dibenzaldehyde-terminated oligo-p-phenylene polyethynylene (OPE) unit , to create an (S3/2, S3/2) N@C60-N@C60 dimer with a fixed spin centre separation of 2.7 nm. The second approach is via a self-assembly scheme in which a Lewis base functionalised N@C60 molecule coordinates to an antiferromagnetic metallic ring magnet to form a (S3/2, S3/2) two-spin centre N@C60-Cr7Ni system with an inter-spin separation of 1.4 nm. In both systems, a significant perturbation of the electron spin transition energies is observed using CW ESR, this perturbation is shown to be well accounted for by the inclusion of an electron-electron dipolar coupling term in the electron spin Hamiltonians. To create entanglement in an ensemble of two-spin centre molecules, the dipolar coupling interaction must lie within a narrow distribution. To achieve this not only the separation but also the orientation of the inter-spin axis with respect to the applied magnetic field must be controlled for which a method of macroscopic alignment is required. The potential of using a uniaxially drawn liquid crystal elastomer to exert uniaxial order on fullerene dimers is tested, finding that the degree of alignment is insufficient, possibly a result of the propensity for the fullerene molecules to phase separate from the elastomer. This phase separation is shown to restrict N@C60 phase coherence lifetime to 1.4 µs at 40 K due to instantaneous spin diffusion. The electron spin environment of both N@C60 and an N@C60-C60 dimer in a polymer matrix is examined using polystyrene as the host matrix. By deuteration of the polystyrene matrix, a maximum phase coherence lifetimes of 48 µs and 21 µs are measured for the N@C60 and N@C60-C60 dimer, respectively. The concept of reading out the electron spin state of N@C60 molecules by coupling it to a spin system that can be probed using optically detected magnetic resonance (ODMR) such as an NV- centre has been previously suggested. To this end, the photostability of N@C60 under 637 nm laser illumination has been examined in solution. The effect of the presence of an atmospheric concentration of oxygen is striking, affording a 57-fold retardation in the photodecomposition of N@C60 compared to a degassed solution. When ambient oxygen is present, the average number of excitations that are required to cause decomposition is ≈60000. Finally, for future UV photophysics experiments involving N@C60, the best solvent to use was found to be decalin, finding that it significantly slowed decomposition of N@C60 in both ambient and degassed solutions. The conclusions of this work make a significant contribution to the field of QIP with N@C60, showing that there is a bright future for N@C60.